School libraries: global trends - Goncalves Dias Gasque, Kelley Cristine; Silva Casarin, Helen de Castro [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2016)
This article discusses the technology and teaching/learning process transformation and the impact of these changes at the school libraries, specifically in terms of collection development, space design and the role of librarians. The literature analysis shows a tendency to adopt learning models based on collaborative construction of knowledge, with an emphasis on understanding learning and teaching activities in several environments. The school libraries can accept and subsidize the varied teaching activities, transforming itself not only in a place of information appropriation, but also in a place where knowledge is produced through connected and diversified collaborative activities. The librarian needs to strengthen their domination of technology in order to obtain, manage, produce and share information. The reading incentive continues to be important but it needs to be expanded to different media and formats.
Keywords: School library; Technology; Learning; Librarian; Collection development